Case series of drug-induced open bite: Extrapyramidal symptoms related to psychotropic medications - Watanabe, Motoko; Tu, Trang Thi Huyen; Takao, Chihiro; Maeda, Chizuko; Nayanar, Gayatri Krishnakumar; Tominaga, Risa; Kimura, Yasuyuki; Takenoshita, Miho; Yoshikawa, Tatsuya; Sumi, Koji; Sumi, Satoko; Motomura, Haruhiko; et al. (Frontiers in Psychiatry, 2023)
Introduction Drug-induced open bite is one of the extrapyramidal symptoms with abnormal tonus of muscles and is rarely recognized in dentistry. This is a retrospective case study to investigate clinical characteristics including detailed complaints in patients with drug-induced open bite. Methods Of the outpatients who first visited the psychosomatic dental clinic at the Tokyo Medical and Dental University Hospital between September 2013 and September 2022, the patients diagnosed with drug-induced open bite were involved in this study. The clinical characteristics including sex, age, detailed complaints, duration of illness, abnormal findings, psychotropic medications, and other medications that were taken at the first examination, psychiatric comorbidities, the duration of psychiatric diseases, and other medical histories were collected retrospectively by reviewing their medical chart. Results Drug-induced open bite was found in 11 patients [women: 7, men: 4, median of age: 49 (36.5, 53) years old]. Difficulty in eating especially chewing was the major complaint (9/11, 81.6%) with the duration of illness as 48.0 (16.5, 66) months. Various degrees of open bite were observed. While some showed no occlusal contact on frontal teeth, some showed occlusal contact only on the second molars; moreover, the jaw showed a horizontal slide in a few patients. Three cases could be followed up for prognosis; while in one case the drug-induced open bite improved with 6 months of follow-up, two cases did not improve, and one showed extrusion of molars. All of them had psychiatric comorbidities with the most common diagnosis being schizophrenia (n = 5) and depression (n = 5) followed by insomnia (n = 1) and autism spectrum disorder (n = 1) including duplicated diagnosis. Nine patients (81.6%) had been undergoing treatment with antipsychotics of which three patients were also taking antidepressants. Discussion Although a drug-induced open bite is a rare symptom, prudent medical interviews about symptoms, psychiatric comorbidities, and psychotropic medication history besides oral assessment are necessary to provide a precise diagnosis and appropriate management in collaboration between dentists and psychiatrists.